Anesthetic Personnel’s Experiences and Perspectives With a National Standard for Safeguarding Anesthesia Practice: A Cross-Sectional Study in Norway - Ann-Chatrin Linqvist Leonardsen; Arvid Steinar Haugen; Johan Ræder; Therese Jenssen Finjarn; Erik Isern; Elin Kismul Aakre; Anne Marie Gran Bruun; Kristoffer Hennum; Jan Petter Ramstad; Tina Sand; Cathrine Saltnes; Svein Arne Monsen (Anesthesiology Research and Practice)
Conclusion: The findings suggest that the NSA is employed in clinical practice. However, assuming the NSA ensures satisfactory anesthetic practice, there are several areas requiring improvement. Given the overlapping roles and responsibilities of anesthesiologists and nurse anesthetists, the NSA may serve as a model for similar guidelines in other countries.